Analisa Privatisasi BUMN di Indonesia - Dwidjowijoto, Riant Nugroho (Jurnal Ilmu Sosial dan Ilmu Politik, 2003)
Policy prescription to privatize the Indonesia state owned entriprises has to be assessed critically. The assumption up. on which the prescription was made in fact cannot be upheld in Indonesia. In prizatization has to be pursued, it must be selectively chosen. The State need to prevent the heavy-burdened public service obligation shoud be prevented from privatization. Moreoever, what is relevant is professionalization, rather than privatization.